Analyzing the Impact of Economic Growth, Poverty, and Unemployment on Income Inequality in Nusa Tenggara Barat Province (2018–2022) - Dewi Riskiani; M. Irwan; Yaya Keho; Sikiru Adedokun (Economy and Finance Enthusiastic, 2024)
Income inequality is a problem that has implications for the welfare of people between regions, where there are differences in income between developed regions and underdeveloped regions. This study aims to determine how much influence economic growth, poverty and unemployment have on income inequality in Nusa Tenggara Barat Province in 2018-2022. This research is a quantitative study using secondary data in the form of panel data obtained from BPS. The method used is panel less square with common effect model. The results of this study show that the economic growth variable has a negative and insignificant effect on income inequality in the province in 2018-2022, the poverty variable has a negative and significant effect on income inequality in the province in 2018-2022, and unemployment has a positive and insignificant effect on income inequality in Nusa Tenggara Barat Province in 2018-2022. Simultaneously, economic growth, poverty and unemployment have a significant influence on income inequality.